Efeitos da adição do IGF-1 ou IGF-LongR3 sobre aspectos celulares e moleculares de complexos cumulus-oócito durante a maturação oocitária in vitro em bovinos - Araujo, Michelle Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The insuline like growth factor-1 recombinant-3 (LongR3-IGF-1) a synthetic analogue of IGF-1 with greater bioavailability has not yet been used in in vitro maturation medium of cumulus-oocyte complexes (COCs). Therefore the aim of this study was to evaluate and compare the effects of LongR3-IGF-1 and insulin-like growth factor-1 (IGF-1) addition in the IVM of bovine oocytes on meiotic progression, apoptosis, and genic expression COCs (GDF9, BMP15, BAX, BCL2, OOSP1, IGFBP2, IGBFP4 e IGFBP5) and their respectively cumulus cells (AREG, EGFR, FSHR, COX2, BAX, BCL2, IGFBP2, IGFBP4 e IGFBP5). Bovine ovaries were collected in slaughterhouse being selected 739 oocytes after aspiration of follicles from 2-8mm diameter. In vitro maturation (IVM) was performed on basic maturation medium containing IGF-1 (100 ng/ml), LongR3-IGF-1 (100ng/ml), and two control groups: 0.1% polyvinyl alcohol (PVA) or 10% fetal bovine serum (FBS), for 22-24 hours in an incubator at 38.5°C and 5% CO2. Subsequently oocytes were denuded and prepared for TUNEL technique, staining Hoechst 33342 and RT-qPCR, intending to evaluate apoptosis, nuclear maturation and gene expression, respectively. Statistical analysis was performed using a linear mixed effects model, which correlated the change in metaphase stage 1 to 2 and the absence of apoptosis among the experimental groups. ANOVA and Tukey tests were used to analyze the results obtained by RTqPCR. After ten replicas of IVM, 339 oocytes (n=5 pools) were evaluated for meiotic progression and apoptosis and 400 (n=5 pools) for gene expression. There was no statistical difference (P>0,05) between the experimental groups with respect to meiotic progression and apoptosis. It was possible to detect mRNA expression of all evaluated genes in the oocyte and its cumulus cells in all experimental groups. There was statistical difference between the group 10% FBS and IGF-1 and LongR3-IGF-1 groups for the expression of gene IGFBP4 in ...

O fator de crescimento semelhante à insulina-1 recombinante-3 (IGF-LongR3), um análogo sintético do IGF-1 de maior biodisponibilidade, ainda não foi utilizado no meio de maturação in vitro (MIV) de complexos cumulus-oócito (CCOs). Portanto, o objetivo deste estudo foi avaliar e comparar os efeitos da adição de IGF-LongR3 e do fator de crescimento semelhante à insulina-1 (IGF-1) na MIV de CCOs bovinos, sobre a progressão meiótica, apoptose e expressão de genes nos oócitos (GDF9, BMP15, BAX, BCL2, OOSP1, IGFBP2, IGBFP4 e IGFBP5) e respectivas células do cumulus (AREG, EGFR, FSHR, COX2, BAX, BCL2, IGFBP2, IGFBP4 e IGFBP5). Ovários bovinos foram coletados em abatedouro, sendo selecionados 739 CCOs após aspiração de folículos de 2-8mm de diâmetro. A MIV foi realizada em meio base de maturação contendo IGF-1 (100ng/mL), IGF-LongR3 (100ng/mL), e dois grupos controles: 0,1% de álcool polivinílico (PVA) ou 10% de soro fetal bovino (SFB), durante 22-24 horas em estufa a 38,5ºC e 5% de CO2. Posteriormente os oócitos foram desnudados e preparados para a técnica de TUNEL, coloração Hoechst 33342 e RT-qPCR, intencionando-se avaliar a apoptose, maturação nuclear e a expressão gênica, respectivamente. A análise estatística foi realizada por um modelo linear de efeitos mistos, o qual relacionou a mudança de estádio de metáfase 1 para metáfase 2 e a ausência de apoptose entre os grupos experimentais, pelo programa lmer4. Os testes ANOVA e Tukey foram utilizados para análise dos resultados obtidos pelo RT-qPCR. Ao final de dez réplicas de MIV foram avaliados 339 (n= 5 réplicas) oócitos quanto à progressão meiótica e apoptose e 400 (n= 5 réplicas) quanto à expressão gênica. Não foi observada diferença significativa (P<0,05) entre os grupos experimentais com relação à progressão meiótica e apoptose. Foi possível detectar a expressão de mRNA para todos os genes avaliados nos oócitos e respectivas células...
Addition effects of IGF-1 or LongR3-IGF-1 on cellular and molecular aspects of cumulus-oocyte complexes during in vitro oocyte maturation in cattle
Keywords: Oócitos; Fertilização in vitro; Expressão gênica; Substancias de crescimento; Técnicas de maturação in vitro de oócitos; Bovino - Reprodução; In Vitro Oocyte Maturation Techniques